Sources of Financial Development and their Effectiveness in the Middle East and North African Region - Falahaty, Manizheh (2011)
Following the relatively poor economic performance and low economic growth experienced by Middle East and North Africa (MENA) countries, many of these nations have implemented financial reforms and structural adjustment programs over the past three decades. A more efficient financial system provides better financial services which enable an economy to increase its GDP growth rate. Conversely, a weakened financial system spills over unfavorably into the economy. With respect to the increase in financial development indicators, economic growth has experienced more fluctuations and has increased albeit weakly over the period 1991-2007. Moreover, mixed results have been obtained from the empirical studies that have focused on this region. Therefore, this study aims to investigate the effectiveness and sources of financial development for the MENA region during 1991-2007, using the Pedroni co-integration technique, cross-sectional dependency test, fully modified ordinary least square (FMOLS) estimation, dynamic OLS (DOLS) estimation and the panel vector autoregressive (PVAR) method. Both banking sector development and stock market development are employed as financial development measures. First, the empirical results of the panel co-integration test reveal that there is a long-run relationship between the financial development indicators and economic growth as measured by real GDP per capita and non-oil GDP per capita. The findings also indicate that each financial sector (the banking sector and stock market) has a unique and different effect on economic growth, where stock market indicators reveal a stronger effect compared to the banking sector indicators. The negative contribution from the banking sector indicators in the financial development process is mainly due to the inefficiency of the credit allocation process, credit regulation and the existence of state owned banking in the MENA region. With respect to the determinants of financial development, the empirical results show that economic growth, openness, bank concentration and institutions have significant and positive effects on financial development in the MENA region. On the other hand, the bank’s ownership structure has had favorable effects on financial development. Finally, in terms of globalization and its effect on institutional reforms, the empirical results using the PVAR and FMOLS methods do not support the hypothesis that globalization affects institutional reforms which promote financial development and economic growth. In fact there is no significant evidence which suggests that there is a relationship between globalization and institutional reform. However, it is interesting to note that the response of institutions to economic globalization is found to be positive and significant. These results indicate that causality may run from economic globalization to institutions. The variance decomposition and general impulse response function also confirmed these results. Therefore the following improvements for the banking sector are provided in order to strengthen the financial development programs and stimulate economic growth. The credit allocation process and credit regulations need to be strengthened and competition in banking sector needs to be reinforced by privatizing the state owned banks. In addition, developing and enhancing growth and liquidity as well as regulatory reforms and increased liberalization in the stock markets is expected to enhance the regional intermediation of resources through the close integration of financial markets which will stimulate economic growth. On the other hand, improving economic growth, financial liberalization and openness policies as well as institutional reforms will encourage the development of financial markets. Also institutional reform policies can be important for accelerating economic globalization and financial development.